Lifelong learning for (re)making future citizens through South Korean curriculum reforms and OECD PISA. Issue 4 (3rd July 2020) - Kim, Jonghun
ABSTRACT: The purpose of the study is to analyze 'systems of reason' that govern the discursive practices constructed in terms of lifelong learning under the name of education reform. This study examined the notion of lifelong learning as a cultural thesis describing modes of life for producing (future) citizens through an analysis of documents from the OECD and South Korea. Along with other OECD member countries, South Korea is deeply involved in a contemporary discourse about educational reform that includes lifelong learning. At the center of this discussion in South Korea, there is an increasing amount of attention being given to comparison, standardization, and school accountability. School accountability in relation to student achievement aims to make citizens more intelligible; it also aims for effective transformations of national education systems and greater productivity and competitiveness nationally. However, (inter)national discourses about lifelong learning are not neutral elements that explain the present and plans for the future, but systems of reason associated with the construction of a particular mode of life for students. Findings of the study suggested that the lifelong learning discourse by the OECD and South Korea embody a particular category for creating particular images and narratives of students and citizens. National boundaries of education systems are now being crossed because of supranational governance of education. Examining the OECD and its influence can draw attention to who the student and the citizen should be and who is excluded from the space of success. By exploring these issues at national and international levels, the study presented how the discourses of the OECD and South Korea are assembled and connected.